Rekognisi Stres Kerja Aparatur Sipil Negara (ASN) Provinsi Banten Selama Masa Pandemi Covid-19 - Wily Mochamad Iqbal; Ipah Ema Jumiati; Rina Yulianti; Delly Maulana (Jurnal Kebijakan Pembangunan, 2022)
The results of the study before the COVID-19 pandemic showed that the prevalence of the Indonesian population experiencing mental-emotional disorders in 2013 was 6.0%. This value increased from 63.33% to 9.8% in 2018. This situation represents that the Indonesian people are vulnerable to psychological or mental-emotional disorders. The existence of the COVID-19 pandemic has resulted in the disruption of the entire system of work mechanisms and social interactions. One of the groups of workers who are at risk of experiencing work stress is the State Civil Apparatus (ASN) at the Leadership Administration Bureau (BAP) of Banten Province. This study aims to measure the level of work stress of ASN in the Bureau for Executive Administration (BAP) of Banten Province. This study aims to measure the work stress scale of ASN in BAP. The results showed the total average score of the work stress level was 2.68, meaning that work stress is in a moderate category which indicates it had enough work stress.